IMPACT OF IMPORT LIBERALISATION ON POVERTY: A DYNAMIC COMPUTABLE GENERAL EQUILIBRIUM AND MICROSIMULATION ANALYSIS FOR GHANA - Obeng, C.K. (UDS International Journal of Development, 2016)
The study examined the long run impact of import liberalization on the incidence, depth and severity of poverty at the national and household levels. The investigation was carried out using a recursive dynamic computable general equilibrium and a microsimulation model calibrated to the 2005 Social Accounting Matrix (SAM) of Ghana. In spite of the strong criticism against import liberalisation as being anti-growth and poverty enhancing, the results showed that the net effect of import liberalisation is a reduction in the incidence, depth and severity of poverty at the national and household levels in the long run. However, the benefits of import liberalisation accrue more to urban households than rural households. The study recommends that import liberalisation must continue to be part of the poverty alleviation strategy of government after 2015 and that government should focus poverty alleviation policies more in the rural areas. Â Keywords: Computable General Equilibrium, Import Liberalization, Microsimulation, Social Accounting Matrix, Poverty